A Comparison of Prognostic Scores (Mayo, UK-PBC, and GLOBE) in Primary Biliary Cholangitis. (4th July 2021) - Goet, Jorn C.; Murillo Perez, Carla F.; Harms, Maren H.; Floreani, Annarosa; Cazzagon, Nora; Bruns, Tony; Prechter, Florian; Dalekos, George N.; Verhelst, Xavier; Gatselis, Nikolaos K.; Lindor, Keith D.; Lammers, Willem J.; et al.
Abstract : INTRODUCTION: Comparative data on scores that predict outcome in primary biliary cholangitis (PBC) are scarce. We aimed to assess and compare the prognostic value of the Mayo Risk Score (MRS, 1989 and 1994), UK-PBC score, and GLOBE score in a large international cohort of patients with PBC. METHODS: Ursodeoxycholic acid–treated patients from 7 centers participating in the GLOBAL PBC Study Group were included. The discriminatory performance of the scores was assessed with concordance statistics at yearly intervals up to 5 years. Model for End-stage Liver Disease was included for comparison. Prediction accuracy was assessed by comparing predicted survival and actual survival in Kaplan-Meier analyses. RESULTS: A total of 1, 100 ursodeoxycholic acid–treated patients with PBC were included, with a mean (SD) age of 53.6 (12.0) years, of whom 1, 003 (91%) were female. During a median follow-up of 7.6 (interquartile range 4.1–11.7) years, 42 patients underwent liver transplantation, and 127 patients died. At 1 year, the concordance statistic for Model for End-stage Liver Disease was 0.68 (95% confidence interval [CI] 0.64–0.72), 0.74 (95% CI 0.67–0.80) for the UK-PBC score, 0.76 (95% CI 0.72–0.81) for the MRS (1989 and 1994), and 0.80 (95% CI 0.76–0.84) for the GLOBE score. The GLOBE score showed superior discriminatory performance, but differences were not statistically different. For all scores, discriminatory performance increased in those with bilirubin >0.6 × ULN and advanced fibrosis estimated with Fibrosis-4. The predicted (median) minus observed 5-year transplant-free survival was +0.4% and +2.5% for the MRS (1989) and GLOBE score, respectively. DISCUSSION: All prognostic scores developed for PBC (GLOBE, UK-PBC, and MRS) demonstrated comparable discriminating performance for liver transplantation or death as well as good prediction accuracy.